31+6n=-5(1-3n)

Simple and best practice solution for 31+6n=-5(1-3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 31+6n=-5(1-3n) equation:


Simplifying
31 + 6n = -5(1 + -3n)
31 + 6n = (1 * -5 + -3n * -5)
31 + 6n = (-5 + 15n)

Solving
31 + 6n = -5 + 15n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15n' to each side of the equation.
31 + 6n + -15n = -5 + 15n + -15n

Combine like terms: 6n + -15n = -9n
31 + -9n = -5 + 15n + -15n

Combine like terms: 15n + -15n = 0
31 + -9n = -5 + 0
31 + -9n = -5

Add '-31' to each side of the equation.
31 + -31 + -9n = -5 + -31

Combine like terms: 31 + -31 = 0
0 + -9n = -5 + -31
-9n = -5 + -31

Combine like terms: -5 + -31 = -36
-9n = -36

Divide each side by '-9'.
n = 4

Simplifying
n = 4

See similar equations:

| 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 | | 4.5*4.4= | | 2x^2=2048 | | 3x(5x-54)= | | -5/9*(-4) | | 17d+104=998 | | 3s+144=531 | | 5(2x-2)=6x+9 | | t-671/11=19 | | 12=336/f | | -39+7x=4x-6(x+8) | | 103-8m=31 | | 36+3h=84 | | 5x-12=2x+14 |

Equations solver categories